Sex-differences in left ventricular remodeling and mechanics after aortic valve surgery in patients with severe aortic valve disease. (14th October 2021) - Singh, G K; Vollema, E M; Prihadi, E A; Regeer, M V; Ewe, S H; Ng, A C T; Mertens, B J A; De Weger, A; Ajmone-Marsan, N; Bax, J J; Delgado, V
Abstract: Background: Sex-differences in left ventricular (LV) remodeling in patients with aortic valve disease have been reported. However, sex-differences in LV remodeling and mechanics in response to aortic valve replacement (AVR) remained largely unexplored. Purpose: The present study aimed to evaluate the sex-differences during the time course of LV remodeling and LV mechanics (by LV global longitudinal strain (GLS)) after aortic valve replacement. Methods: Patients with severe aortic valve disease (aortic stenosis (AS) or aortic regurgitation (AR)) undergoing AVR with echocardiographic follow-up at 1, 2, and/or 5 years were evaluated. LV mass index, LV ejection fraction, LV GLS and stroke volume (SV) were measured. Linear mixed models analyses were used to assess changes in LV mass index, LVEF, LV GLS and SV between time points. The models were corrected for age, LV end-diastolic diameter at baseline and time between echocardiograms. Results: A total of 211 patients (61±14 years, 61% male) with severe aortic valve disease (AS 63% or AR 39%) were included. Before AVR, men had larger LV mass index and higher SV compared to women. Both men and women had a preserved LV ejection fraction (54±12 and 56±9, P=0.102, respectively), but moderately impaired LV GLS (14.6±4.1 and 16.1±4.1, P=0.009, respectively). After AVR, both groups showed LV mass regression, improvement in LV ejection fraction and LV GLS. LV mass index and SV remained higher in men. During follow-up women showed significantly better LV GLS compared to men (P=0.030, figure 1). Conclusion: In men and women with severe aortic valve disease undergoing AVR, the time course of changes in LV mass regression, LV ejection fraction, LV GLS and SV are similar. During follow-up LV mass index remained larger in men and women showed significantly better LV GLS. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The department of Cardiology received unrestricted research grants from Abbott Vascular, Bayer, Bioventrix, Biotronik, Boston Scientific, Edwards Lifesciences, GE Healthcare and Medtronic. Victoria Delgado received speaker fees from Abbott Vascular, Edwards Lifesciences, GE Healthcare, MSD and Medtronic. Nina Ajmone Marsan received speakers fees from Abbott Vascular and GE healthcare. Jeroen J Bax received speaker fees from Abbott Vascular. The remaining authors have nothing to disclose.